THE EFFECTIVENESS OF USING PICTURE SERIES IN TEACHING WRITING NARRATIVE TEXT OF EIGHTH GRADE STUDENTS OF SMP NEGERI 1 NGANTRU IN THE ACADEMICYEAR 2014/2015 - Reta, Nike E. Angga; Gumilang, Willy Anugrah; Huda, Moh. Choirul (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2016)
Writing gives us unique opportunities to explore ideas andinformation. By writing, we care to subjects well and make them our own.In relation to using instructional media in learning writing, the use ofpictures series can be a choice as one of many alternative ways to helpstudents learn writing. Pictures and all of their form for instance pictures ofstory, There are a lot of language activities that can be done using picturesseries. This research used experimental research. The researcher used onegroup pretest posttest design which one of pre experimental research. Thesubject of the study is the eighth grade students of SMPN 1 Ngantru in theacademic year of 2014/2015. There were 33 students. The technique usedfor collecting data is pre-test and post-test and interview. Based on theresult of data, mean of pretest score is 73,03 and mean of Post Test score is84,5. It means that posttest score was higher than pretest. The result of thestudy was that the students’ progress during teaching and learning activityby using picture series in teaching writing narrative texts to effect writingskill was good. In the T-Test result, T-value = 6.424 2.0369 (T- table).The significance level 0,05. So, the Ho was rejected and Ha was accepted.KEY WORDS: Picture series and Narrative text